Rehabilitation of therapy-related cognitive deficits in patients with breast cancer - Weis, Joachim; Poppelreuter, Martin; Helge Bartsch, Hans (Psicooncología, 2012)
Among various side effects of adjuvant chemotherapy neuropsychological deficits have been described within the last two decades. A literature review shows that especially breast cancer women after adjuvant chemotherapy are suffering from these deficits. Against this background the need for special rehabilitation programms has been discussed to help the patients to cope with this sequelae, but there are only few attempts for special neuropsychological training programms for cancer patient. In the study presented we compared two types of neuropsychological interventions in a rehab setting against a control group with no specific training in a total of 96 female in-patients undergoing inpatient oncological rehabilitation. Most results of a comprehensive neuropsychological test battery improved significantly during the patients’ oncological rehabilitation in all three groups, whereas we could not identify a specific intervention effect neither between the two intervention groups nor between the treatment and control groups. In terms of the follow-up examination we found that clinically relevant neuropsychological deficits were still evident 6 months later in a small subgroup of patients
Keywords: Breast cancer; neuropsychological rehabilitation; cognitive deficits; side effects of chemotherapy; late effects of treatment.